A Random Key Generation Approach for Rijndael Algorithm - Hmood, Dalal Naeem (Al-Nahrain Journal of Science, 2012)
One of security interlocution is data encryption/decryption whenever data being sent over communication lines may be protected by encrypting the message, that can be decrypted only by the authorized person receiving the message. In this paper a simple and fast approach is proposed to modify the key generation of Rijndael algorithm. The proposed approach uses randomize to generate a fixed key enough for the block size and number of rounded. The proposed approach has been implemented successfully in interlocution system on different amount of ciphertext length.